Integration of Life Skills In Extracurricular Sports for Positive Youth Development - Heriwando, Heriwando; Ma’mun, Amung (ASEAN Journal of Sport for Development and Peace, 2024)
Extracurricular activities are activities that are carried out outside of class hours or outside the main curriculum. Extracurricular activities have been believed to have a positive influence on students in developing their potential. The aim is to develop their interest and maintain their motivation in learning to increase student engagement develop social abilities, provide new skills, increase independence, and shape personality character. In line with the context of Positive Youth Development (PYD), extracurricular activities have many positive benefits for students involved in their activities, namely increased life skills, social interaction, and concern for the environment. The design used was a literature review, articles were collected from accredited national and international journals. The criteria for the articles used were articles published in 2012-2023. Based on the articles collected, it was found that extracurricular activities were able to hone self-ability, independence, social skills, strengthen a sense of community towards peers and teachers. Extracurricular sports activities can also increase self-confidence and encourage students' academic progress, and help life skills in setting goals and managing emotions. Through extracurricular sports activities, life skills can be acquired in the form of caring in dealing with everyday life situations. Extracurricular sports have a positive influence on the development of adolescent children in growing and developing in a positive direction.